Association of rs10507391 polymorphism with the development of acute cerebrovascular event. (14th October 2021) - Chernova, A; Nikulina, S; Nikulin, D
Abstract: Purpose: To study SNP rs10507391 association (A> T) with development of Acute Cerebrovascular Event in the patients with cardiovascular pathology and risk factors of its development who are representatives of the east Siberian population. Material and methods: 260 patients with Acute Cerebrovascular Event participated in a research (age [57.0; 51.0–62.0]) and 272 patients of control group (age [55.0; 51.0–62.0].). Among the patients who transferred Acute Cerebrovascular Event, 157 men and 103 women. The control group included 170 men and 102 women. Inspection of the main group included: collecting complaints, anamnesis, clinical examination, computer tomography of a brain, electrocardiography, echo, ultrasonic of arteries, daily monitoring of arterial blood pressure and cardiac rhythm, analysis of a coagulant system of blood. Patients of the main group had the following cardiovascular pathology and risk factors: arterial hypertension, supraventricular tachycardia, dislipidemiya, atherosclerosis brachiocephalic of arteries, disturbances of a system of a hemostasis. The control group is examined within the international HAPIEE project. The molecular and genetic research was conducted by PCR method in real time. Statistical processing of material was carried out with use of set of the Statistica for Windows 7.0, Excel and SPSS 22 application programs. Results: When studying SNP rs10507391 association (A> T) connection between a rare genotype of a TT and an allele of T and the increased risk of Acute Cerebrovascular Event is established with development of Acute Cerebrovascular Event in all analyzed groups and subgroups of patients. Conclusion: A genotype of a TT and an allele of T of SNP rs10507391 (A> T) increases risk of development of an acute disorder of cerebral circulation in patients regardless of the previous cardiovascular pathology and risk factors, including at patients with arterial hypertension, supraventricular tachyarrhythmias, atherosclerosis the brachiocephalic of arteries, disturbance of lipidic exchange and the system of a hemostasis. Funding Acknowledgement: Type of funding sources: None.